The Relationship of Peer Social Support with Academic Self Efficacy - Nabila Permata Yuri; Frischa Meivilona Yendi; Zadrian Ardi (Jurnal Neo Konseling, 2020)
Students in university with the complexity of the lecture system are characterized by course credit which is an education organizer system to declare the burden of students, learning experiences, and the burden of administering the program. All of that must be done by students with belief in their abilities or called selfefficacy. Students who have high self efficacy will provide all the abilities they have to achieve what is expected. The expectation to achieve what is desired is not uncommon for students to find obstacles, for that a student gets a social support in order to convince himself to be able to survive and achieve it. Social support obtained by students can come from peers, with the social support of peers will affect the ability of students in university. This research is a descriptive correlational study, with 31 students as samples obtained using purposive samplaing techniques. Data correlation instrument used a scale questionnaire that was compiled by itself in data collection using Google forms. The result of this research indicate that most students get low social support from their peers. Furthermore, the research findings also show that most students have moderate academic self efficacy.